2012
DOI: 10.7314/apjcp.2012.13.11.5599
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of Key EGFR Pathway Genes in Chinese Breast Cancer Patients

Abstract: Background: The epidermal growth factor receptor (EGFR) is a potential therapeutic target for breast cancer treatment; however, its use does not lead to a marked clinical response. Studies of non-small cell lung cancer and colorectal cancer showed that mutations of genes in the PIK3CA/AKT and RAS/RAF/MEK pathways, two major signalling cascades downstream of EGFR, might predict resistance to EGFR-targeted agents. Therefore, we examined the frequencies of mutations in these key EGFR pathway genes in Chinese brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 35 publications
2
12
0
Order By: Relevance
“…A recent report also found the similar finding in breast cancer in where only 7.76% of patients showed codon 12 mutations in breast cancer and associated with Her-2 (Pereira et al, 2013). Even in Chinese population where they found only 2.5% which much lower than pancreatic and colorectal cancers (Tong et al, 2012).…”
Section: Discussionsupporting
confidence: 56%
“…A recent report also found the similar finding in breast cancer in where only 7.76% of patients showed codon 12 mutations in breast cancer and associated with Her-2 (Pereira et al, 2013). Even in Chinese population where they found only 2.5% which much lower than pancreatic and colorectal cancers (Tong et al, 2012).…”
Section: Discussionsupporting
confidence: 56%
“…As previously reported, the mutation rates and spectra of TP53 and PIK3CA are quite different among different populations. For PIK3CA mutations in Chinese population, the mutation rates were 12.3% (7/57) reported by Wang and colleagues (23) and 7.5% (9/120) reported by Tong and colleagues (24). For TP53 mutations, the frequency of mutation reported by Hao and colleagues (25) was 22.7% (10/44), which was consistent with the results from Fukushima and colleagues (26), who reported 20.0% (10/50) of the tumors harboring TP53 mutations in the Japanese population.…”
Section: Discussionmentioning
confidence: 67%
“…Studies that included small numbers of MC demonstrated that mutated PIK3CA, which is found in 16-33% of IDCs, is not a common finding in MC (0-13%), supplementary material, Figure S8 [125,[152][153][154][155][156][157]. Mutations of BRAF and KRAS are not common in breast cancer (0-3% and 2-5%) and associations with MC have not been studied [65,158,159]. Unlike in colorectal MC, MSI is a rare phenomenon in MC of the breast, occurring only sporadically (0-3%) [160][161][162][163][164][165].…”
Section: Mucinous Breast Carcinomamentioning
confidence: 99%